Perancangan Layout Gudang Bahan Pembantu PT. Sun Paper Source dengan Penerapan Metode Class Based Storage - Hendra Santoso Wijaya; Herri Christian Palit (Jurnal Titra, 2021)
PT Sun Paper Source’s operational warehouse is used for store supporting materials and finished goods in pallet units. A significant increase of supporting material’s pallet in 2020 resulted in the warehouse's overcapacity, this problem may affect warehouse activities in the future. The increase of supporting material’s pallet was affected by the surge of production tonnage and finished good’s Stock Keeping Unit (SKU), which has risen significantly by 117 units (28,1 % year to date). Therefore, the company plans to build a specific supporting material’s warehouse with a total area of 1530 m2. The objective of this research is to design a warehouse layout with the implying of class based storage method. The maximum on hand inventory value throughout 2020 will be used as a reference to determine how much slot pallet needed. The placement of supporting materials based upon throughput per space value, the highest value will be placed closer to the exit door (I/O). Slotting process of each supporting material will be assisted by the implementation of ABC classification. The warehouse layout design is estimated to accommodate 704 pallets. This design generates a 95.09% on block utility value and resulted in 179,312.3 m of total distance travelled per year.